Effect of dietary supplementation of wildCumin (Bunium persicum) seeds on performance, nutrient digestibility and circulating metabolites in broiler chicks during the finisher phase. Issue 5 (3rd October 2022) - Shuaib, Muhammad; Ullah, Nasr; Hafeez, Abdul; Alhidary, Ibrahim A.; Abdelrahman, Mutassim M.; Khan, Rifat Ullah
Abstract: The objective of the present study was to evaluate the impact of inclusion of wild cumin seeds (WCS) on performance, nutrient digestibility and blood profile in broilers during the finisher phase. For this purpose, 360, 14 days old chicks were randomly divided into four groups designated as CONT (control), 0.5WCS, 1.0WCS and 1.5WCS with 5 replicates, which were supplemented with WCS at the rate of 0, 0.5, 1, and 1.5% respectively. On the overall, feed intake was significantly ( p < 0.01) higher in the CONT compared to the 1.0WCS. At the end of the finisher phase, and overall basis, body weight and feed conversion ratio were significantly ( p < 0.05) higher in 0.5WCS. Crude protein apparent digestibility in the ileum was significantly ( p < 0.05) higher in 0.5WCS compared to the CONT, while crude fat digestibility was significantly ( p < 0.01) higher in 0.5WCS and 1.5WCS compared to the control. Similarly, serum triglyceride was significantly ( p < 0.05) lower in 0.5WC but high density lipoprotein was significantly ( p < 0.05) higher in the same group. It was concluded that wild Cumin at the rate of 0.5% was superior compared to the other treatments in the diet to improve the performance, nutrient digestibility and blood metabolites in broiler during the finisher phase.